FUEL CELLS: CONTAMINATION AND RECENT ADVANCEMENTS FOR ITS STABILIZATION - Kumar, Manish; Raj, Aniket; Srivastava, Prateek (MATTER: International Journal of Science and Technology, 2019)
A Fuel cell will soon be a very robust weapon to replace current highly carbonized fossil fuel generation of electricity by a more cleaner and efficient source of generation. The kind of electricity generation that is being used nowadays impacts environment badly and contributes to Global Warming. In this context, Fuel Cell can prove to be significant in generation of cleaner energy. In addition to this, fuel cell is more efficient as it doesn’t operate as any heat engine; so not bound up to Carnot efficiency. Certain impurities either from the fuel that is being supplied or from the environment might result into undesirable reactions that cause fuel cell contamination. This becomes the reason for the dramatic drop in the performance of a fuel cell that has been observed from our working "Solar Hydrogen Plant"Fig A model. For testing and extending the life of a fuel cell by detecting and mitigating the cause of degradation, the researchers has passed the sample of distilled water and Ultra-pure water (Type I) after electrolysis through Ion Chromatographer, Total Dissolved Solid test, Electrical Conductivity Test, and pH test. The cell has been allowed to run in the lush green campus of Banaras Hindu University whose environmental conditions are considered to be less polluted in the Varanasi. Henceforth, the researchers also tested atmospheric situations and its effect on fuel cell. The results of this paper will be useful in designing a device which can mitigate contamination and will ensure successful domestication of Fuel cell. In this paper, various methods of obtaining pure hydrogen gas like Pressure Swing Adsorption (PSA), High & Low Temperature Diffusion, Solvent absorption of CO and CO2 are also discussed. . A new model of fuel cell installation is also discussed with an additional stage of hydrogen fuel filtration using PSA, TSA to supply hydrogen fuel with purity up to 99.8%.